Habituation of mathematical literacy trained in junior high school - Rachmaningtyas, Nur Anisyah; Kartowagiran, Badrun; Sugiman; Heri Retnawati; Hassan, Aminuddin (Eurasian Society of Educational Research, 2022)
The importance of literacy is a competency requirement that must be possessed by students to face competition in the 21st century. This is directly related to the extent to which students' scientific thinking processes understand and solve problems. This study aims to describe how literacy is trained in learning in junior high schools. The approach used is a qualitative approach with the type of phenomenological research. The participants in this study were 5 junior high school teachers who teach in the Special Region of Yogyakarta. Data was collected through virtual interviews with the help of the Google Meet platform. The data analysis model used is the model of Bogdan and Biklen with data collection procedures, data reduction, verification and conclusion. The results showed that literacy was trained on students with the habit of reading textbooks for 15 to 30 minutes every day by reporting their readings in student journals, teacher efforts in changing project and problem-based learning methods and strategies according to student conditions, and teacher habituation in providing HOTS level questions to train students' critical thinking processes, balance theoretical understanding and understand the surrounding environment.